Sexual sensation-seeking, hypersexuality, and risky sexual behaviors between adults with and without ADHD symptoms - Vandewalle, Márcia (2022)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder defined by disabling levels of inattention, disorganization and/or hyperactivityimpulsivity that may interfere in diverse areas of functioning across various stages of the human development. Impulsivity emerges as an important longterm symptom in ADHD – having a strong genetic basis with evidence of altered reward processing and dopaminergic dysfunction – and may increase sexual risk behavior during adulthood [1,2]. Although some studies have shown adolescents with ADHD to exhibit more sexual risk behavior and higher levels of sensationseeking and impulsivity, a lack of similar studies in the adult population exists The objective of this study was to compare sexual sensation seeking, hypersexuality and sexual risk behaviors in adults with and without symptoms of ADHD.